Algorithms for external tracking of an AUV - Aníbal Matos (2004)
In this paper we describe the algorithms used in the external tracking system of the Isurus AUV. By listening to the acoustic signals exchanged between the vehicle and the beacons of the acoustic navigation network, the tracking system is able to obtain distance measurements from the vehicle to each beacon, that are then used to compute the vehicle horizontal position. Several error sources make these measurements inadequate to be used for computing the vehicle position by a simple triangulation technique. The tracking algorithms described here are able to reject highly erroneous measurements, producing position estimates with a satisfactory degree of accuracy.